Cultivation of Cassava and Moringa Based on Ecoenzymes as an Effort to Prevent Stunting in Dry Land Areas - Sitawati, Sitawati; Zuhriyah, Lilik; Prasetyorini, Linda; Ariani, Ariani; Wardani, Diajeng Setya; Azzahra, Shabrina Laila; Wicaksana, Anang Panca (Journal of Agriprecision & Social Impact, 2025)
The use of ecoenzyme-based solutions (EE) is one innovation in supporting sustainable food security in drylands. This research and community service project was conducted in Putukrejo Village, Kalipare District, Malang Regency, with the aim of increasing the productivity of cassava and moringa plants while supporting stunting prevention. Ecoenzymes were obtained from the fermentation of household organic waste, brown sugar, and clean water fermented for three months. The solution was applied to cassava and moringa at a dose of 15 per tree dissolved in one liter of water, applied weekly. The results showed an increase in the vegetative growth of moringa and cassava compared to the control group. From a socio-economic perspective, this technology improves the community's skills in production and opens up business opportunities for cassava and moringa-based food products. These findings are in line with the achievement of SDGs 2 (Zero Hunger) and SDGs 12 (Responsible Consumption and Production).